2018
DOI: 10.1371/journal.pone.0199740
|View full text |Cite
|
Sign up to set email alerts
|

Potential involvement of neutrophils in human thyroid cancer

Abstract: BackgroundNeutrophil functions have long been regarded as limited to acute inflammation and the defense against microbes. The role(s) of neutrophils in cancer remain poorly understood. Neutrophils infiltrate tumors and are key effector cells in the orchestration of inflammatory responses. Thyroid cancer (TC) is the most recurrent endocrine malignant tumor and is responsible for 70% of deaths due to endocrine cancers. No studies are so far available on the role of neutrophils in TC.ObjectiveOur purpose was to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 89 publications
2
66
1
Order By: Relevance
“…The proportion of immune cells in the TME is also favoring tumor-promoting immune cells. The elevation of TAMs, DCs, MCs, neutrophils, NK cells, and Tregs in PTC has been reported [31][32][33][34][35][36][37][38][39][40]. Our study found that these tumor-promoting immune cells were recruited in large numbers in PTC and exhibited a tumorpromoting immune microenvironment phenotype.…”
Section: Discussionsupporting
confidence: 73%
“…The proportion of immune cells in the TME is also favoring tumor-promoting immune cells. The elevation of TAMs, DCs, MCs, neutrophils, NK cells, and Tregs in PTC has been reported [31][32][33][34][35][36][37][38][39][40]. Our study found that these tumor-promoting immune cells were recruited in large numbers in PTC and exhibited a tumorpromoting immune microenvironment phenotype.…”
Section: Discussionsupporting
confidence: 73%
“…One potential mechanism of T cell exclusion is the interaction of LAG3 and GAL3. Studies have shown that the interaction between LAG3 and GAL3 in the tumor microenvironment leads to T cell suppression (Kouo et al 2015) and that the recruitment of T cells may be decreased in GAL3-high tumors (Gordon-Alonso et al 2017). In assessing the immune signatures of DC low and high tumors, we find that the LGALS3/LAG3 ratio is significantly higher in activated DC high tumors, suggesting that this may be a potential mechanism for the immune exclusion environment.…”
Section: Figurementioning
confidence: 64%
“…Finally, neutrophils have been shown to be important for metastasis in multiple cancer types, including melanoma (Soler-Cardona et al 2018), breast cancer (Wculek & Malanchi 2015) and gastric cancer (Hiramatsu et al 2018). Recent literature also suggests involvement of neutrophils Endocrine-Related Cancer in the growth of thyroid carcinomas (Galdiero et al 2018). While the mechanism of neutrophil-mediated enhancement of metastasis is unclear, some studies suggest that neutrophils inhibit CD8 T cells and may attract metastatic cells to new sites (Coffelt et al 2015, Wculek & Malanchi 2015.…”
Section: Discussionmentioning
confidence: 99%
“…(13). As well as thyrocytes, these models have been developed to include co-culture with immune cells such as macrophages (14) and neutrophils (15).…”
Section: Figure 4 | (A)mentioning
confidence: 99%
“…The oxygen and nutrient diffusion gradient present within a spheroid structure can promote migration and invasion through changes in gene expression-not present in 2D culture models. The effect of co-cultured cells such as macrophages on migration and invasion of thyroid cancer cells has also been explored as these immune cells have roles in epithelial-mesenchymal transition and subsequent tumor progression (14,15). These assays are also applied in research studies testing the cytotoxic effects of chemotherapy agents.…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%